Factors Of Using The Spiritual Heritage Of Great Teacher Scientists In The Development Of Students' Educational Research Competences - Kattayeva Gulnoza Komilevna (Zien Journals, 2024)
This article describes the use of the heritage of great mudarris scientists in the development of students' educational research competencies.
Keywords: heritage; mudarris; alloma; culture